Pengaruh Kualitas Informasi, Celebrity Endorsement, dan Sikap Konsumen pada Program Flash Sale terhadap Minat Beli di Aplikasi Tiktok - Zalzalah, Guruh Ghifar; Febriyanto, Deka (Universitas Proklamasi 45, 2023)
This study intends to find out the impact of information quality, celebrity endorsements, and consumer attitudes on flash sale programs on purchase intention in the TikTok application, either partially or simultaneously. This research is a quantitative study using multiple linear regression analysis techniques which was carried out using the help of the SPSS 25 program. Data collection used a questionnaire, samples were consumers who are domiciled in the Special Region of Yogyakarta and used the Tiktok application with a total of 100 respondents. The results of this study concluded that partially the quality of information, celebrity endorsements, and consumer attitudes in flash sale programs have a positive impact on purchase intention.